دور المشرفات التربويات لرياض الأطفال في تطوير أنماط التعليم الحديثة لدى معلمات رياض الأطفال داخل الخط الأخضر فى منطقة الشمال - خلايلة، ربحية يوسف عيسى; الشرمان، منيرة محمود; عليمات، صالح ناصر Aliymat, Saleh (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2018)
هدفت الدراسة إلى تحديد دور المشرفات التربويات لرياض الأطفال داخل الخط الأخضر في منطقة الشمال في تطوير أنماط التعليم الحديثة لدى معلمات رياض الأطفال، وقد تكونت عينة الدراسة من (306) معلمة تم اختيارهن من خلال الطريقة العشوائية البسيطة، أخذت بطريقة عشوائية من مجتمع الدراسة المكون من (1531) معلمة، ولتحقيق أهداف الدراسة طورت الباحث استبانة أنماط التعلم، وتكونت من (20) فقرة، توزعت على أربعة مجالات، وتم التأكد من صدقها وثباتها، وتوصلت الدراسة إلى أن: - استجابات معلمات رياض الأطفال داخل الخط الأخضر في منطقة الشمال على مجالات استبانة أنماط التعلم قد جاءت ضعيفة ولجميع المجالات. - وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (a ≤ 0.05) في دور المشرفات التربويات تبعا للمركز الوظيفي في بعد التعلم بالاكتشاف لصالح المعلمات المكملات. - وجود فروق ذات دلالة إحصائية في متغير الخبرة عند مستوى الدلالة (a ≤ 0.05) في دور المشرفات التربويات في بعد التعلم بالاكتشاف لصالح المعلمات اللواتي تقع خبرتهن تحت 10 سنوات. - وجود فروق ذات دلالة إحصائية في دور المشرفات التربويات في متغير المؤهل العلمي عند مستوى الدلالة (a ≤ 0.05) في بعد التعلم باللعب وبعد التعلم بالاكتشاف تبعا لمتغير المؤهل العلمي ولصالح المعلمات الحاصلات على دراسات عليا. The study aimed at determining the role of educational supervisors for kindergartens within the Green Line in the North region in the development of modern education patterns among kindergarten teachers. The study sample consisted of (306) teachers who were selected through the simple random method, (1531) teachers. To achieve the objectives of the study, the researcher developed a questionnaire of learning styles, consisting of (20) paragraphs, divided into four fields, and verified its validity and stability. The study concluded that The responses of Kindergarten teachers within the Green Line in the North region on areas of learning patterns identification have been weak and for all areas There were statistically significant differences in the functional status at the level of significance (α ≤ 0.05) in the after learning of discovery in favor of the supplementary parameters There were statistically significant differences in the experience variable at the level of significance (a ≤ 0.05) in the after learning of discovery for the benefit of the teachers whose experience is under 10 years -There were statistically significant differences in the scientific qualification variable at the level of significance (a ≤ 0.05) in the distance of learning by play and after learning by discovery according to the variable of the scientific qualification and for the benefit of the female graduates with postgraduate studies.
Keywords: الاستراتيجيات التربوية -- المشرفات التربويات -- معلمات رياض الأطفال -- السعودية